ACTIVITY AND ISOLATION OF THE ALLELOPATHIC COMPONENTS OF GMELINA (GMELINA ARBOREA ROXB) EXTRACTS AGAINST POPPING POD (RUELLIA TUBEROSA) AND CORN (ZEA MAYS L.) - Alburo, Rosalyn P.; Alburo, Hemres M.; Ramal, Allan A.; Suico, Ma. Ligaya (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 18 No. 2, 2015, 2018)
Please see PDF file.